Descriptive writing skills in the influencer era: sentiment effects of digital content - Agus Salim Lamusu; Hasna Nurain Mukhsin; Alter Lasarudin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study investigates the influence of influencer-generated digital content on university students’ descriptive writing skills, with a focus on the role of sentiment and digital literacy. Employing a quantitative cross-sectional design, data were collected from 63 students at Universitas Muhammadiyah Gorontalo and IAIN Sultan Amai Gorontalo using questionnaires and semi-structured interviews. Students’ perceptions of writing quality were analyzed in relation to their exposure to digital content with positive, neutral, and negative sentiment. The findings reveal a significant correlation between exposure to positive-sentiment content and perceived improvements in creativity, vocabulary use, and idea organization, while neutral and negative content is associated with more formal but less expressive writing. The study also indicates that digital literacy mediates how students adapt informal digital language to academic writing demands. These results suggest that integrating digital literacy into writing instruction is essential to help students navigate the influence of digital media on academic writing.